The Value of Biopsy in Histopathological Diagnosis - Akhrorkulovich, Ismatov Tuichiboy; Makhsudovich, Kurbonov Obid; Oltinbaevich, Makhmudov Kodirbai (Health & Medical Sciences, 2024)
In this prospective study, 78 renal biopsies were performed: 46 men and 32 women. The average age of men was 37 ± 18.3 years, and that of women was 24.6 ± 13.8 years. Most often, biopsy was performed in the age group from 19 to 48 years among both men (58.6%) and women (66.7), respectively. The most common age group undergoing biopsy was between 19 and 48 years of age for both men (76.1%) and women (78.1%). There were 18 patients over 45 years of age (23.1%): 11 men and 7 women. The primary reason for renal biopsy was the presence of proteinuria with hematuria and subnephrotic proteinuria in 26 patients, followed by nephrotic syndrome in 12 patients. IgA nephropathy emerged as the most frequently identified histopathological diagnosis, accounting for 17.7% of cases. Conversely, minimal change disease, the second most prevalent histopathological finding at 10.4%, was identified in patients with nephrotic syndrome; their renal biopsies appeared normal under histological examination due to the absence of electron microscopy analysis. Nephrosclerosis ranked as the third most common histopathological diagnosis among patients at 6.7%. Additional findings included focal segmental glomerulosclerosis (7.3%), membranous glomerulonephritis (7%), mesangiocapillary glomerulonephritis (7%), and chronic graft rejection (2.6%) in two patients with accompanying fasting and transplant azotemia. Acute tubular necrosis and chronic interstitial nephritis were each present in 1.3% of patients, while 9.0% of cases yielded inconclusive results, indicating either a blood clot or brain tissue in the biopsy samples.